Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan pada Tax Avoidance - Riskatari, Ni Ketut Rai; Jati, I Ketut (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p07, 2020)
Tax avoidance is an effort made by taxpayers to reduce tax debt legally by utilizing loophole from tax regulations. Tax avoidance is a unique and complicated problem, on the one hand tax avoidance is allowed but on the other hand tax avoidance is not desired by the government. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The sample selection in this study uses a purposive sampling technique with predetermined criteria and a sample of 22 companies is obtained. The data analysis technique used is multiple linear regression analysis. The hypothesis testing method uses a significance level of 5 percent. Based on the results of the study indicate that the profitability variable has a negative effect on tax avoidance, leverage variable has a positive effect on tax avoidance and company size has a positive effect on tax avoidance. Keywords: Tax Avoidance; Profitability; Leverage; Firm Size.